Compliance and tolerability of short-course radiotherapy followed by preoperative chemotherapy and surgery for high-risk rectal cancer – Results of the international randomized RAPIDO-trial. (June 2020) - van der Valk, Maxime J.M.; Marijnen, Corrie A.M.; van Etten, Boudewijn; Dijkstra, Esmée A.; Hilling, Denise E.; Kranenbarg, Elma Meershoek-Klein; Putter, Hein; Roodvoets, Annet G.H.; Bahadoer, Renu R.; Fokstuen, Tone; ten Tije, Albert Jan; Capdevila, Jaume; et al.
Highlights: Patients with high-risk rectal cancer are generally treated with chemoradiotherapy followed by surgery. Compliance of postoperative chemotherapy in rectal cancer patients is known to be low. In this study patients were randomized to the standard treatment of chemoradiotherapy or short-course radiotherapy followed by chemotherapy prior to surgery. Short-course radiotherapy and preoperative chemotherapy was associated with considerable toxicity. Yet, high compliance of systemic therapy could be achieved by giving it after short-course radiotherapy and prior to surgery. There were no differences in the details of surgical procedures or postoperative complications. Abstract: Background: Preoperative chemoradiotherapy (CRT) followed by total mesorectal excision is widely accepted as the standard of care for high-risk rectal cancer. Adjuvant chemotherapy is advised in several international guidelines, although the survival benefit remains unclear and compliance is poor. The current multidisciplinary approach has led to major improvements in local control, yet the occurrence of distant metastases has not decreased accordingly. The combination of short-course radiotherapy (SCRT) and chemotherapy in the waiting period before surgery might have several benefits, including higher compliance, downstaging and better effect of systemic therapy. Methods: This is an investigator-initiated, international multicentre randomized phase III trial. High-risk rectal cancer patients were randomized to SCRT followed by chemotherapy (6 cycles CAPOX or alternatively 9 cycles FOLFOX4) and subsequent surgery, or long-course radiotherapy (25–28 × 2–1.8 Gy) with concomitant capecitabine followed by surgery and optional postoperative chemotherapy (8 cycles CAPOX or 12 cycles FOLFOX4) according to local institutions' policy. The primary endpoint is time to disease-related treatment failure. Here, we report the compliance, toxicity and postoperative complications in both study groups. Findings: Between June 2011 and June 2016, 920 patients were enrolled. Of these, 901 were evaluable (460 in the experimental arm and 441 in the standard arm). All patients in the experimental arm received 5 × 5 Gy radiotherapy, and 84% of all patients received at least 75% of the prescribed chemotherapy. In the standard arm, the compliance for CRT was 93% and 58% for postoperative chemotherapy. Toxicity ≥grade 3 occurred in 48% of patients in the experimental arm, compared to 25% of patients in the standard arm during preoperative treatment and 35% of patients during postoperative chemotherapy. No statistically significant differences in surgical procedures or postoperative complications were observed. Interpretation: High compliance (84%) of preoperative systemic treatment could be achieved with the experimental approach. Although considerable toxicity was observed during preoperative therapy, this did not lead to differences in surgical procedures or postoperative complications. Longer follow-up time is needed to assess the primary endpoint and related outcomes.